2001
DOI: 10.1037/h0095069
|View full text |Cite
|
Sign up to set email alerts
|

Working toward recovery in New Hampshire: A study of modernized vocational rehabilitation from the viewpoint of the consumer.

Abstract: Following the passage of the ADA and the Rehabilitation Amendments of 1992, vocational rehabilitation services offered by New Hampshire community mental health centers have striven collectively to streamline the efficiency of their interventions. Evolved versions of the two most frequently utilized modalities are compared, by measuring vocational satisfaction as it is rated by the perspective of the consumer. Both methods are found to be highly effective, but differ greatly in the nature of their impact and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Thisstudy'sfinalareaofemphasiswasperceivedefficacy ofservices.Bothstaffandclientsreportedhighlevelsnot onlyofsatisfactionwithbutalsoofthebenefitsofoccupationaltherapyservicesrelatedtoimprovedindependenceand overallwellness.Theprimarycontributortoclientsatisfac-tionandperceivedefficacyofserviceappearedtobePRC's unique culture and the therapist-client relationship. The existing literature has suggested that clients tend to have increased satisfaction when supported by their therapists (Young, 2001). In addition, clients value therapists who demonstrateinterestintheirviewsandcanclearlycommunicatestrategiestohelpclientsmeettheirgoals (McKinnon, 2000).Boththerapistsandclientswhoparticipatedinthe studyspoketotheimportanceofcollaborationthroughout thetherapeuticprocessinachievingpersonalmeaningand goalattainment.…”
Section: Discussionmentioning
confidence: 99%
“…Thisstudy'sfinalareaofemphasiswasperceivedefficacy ofservices.Bothstaffandclientsreportedhighlevelsnot onlyofsatisfactionwithbutalsoofthebenefitsofoccupationaltherapyservicesrelatedtoimprovedindependenceand overallwellness.Theprimarycontributortoclientsatisfac-tionandperceivedefficacyofserviceappearedtobePRC's unique culture and the therapist-client relationship. The existing literature has suggested that clients tend to have increased satisfaction when supported by their therapists (Young, 2001). In addition, clients value therapists who demonstrateinterestintheirviewsandcanclearlycommunicatestrategiestohelpclientsmeettheirgoals (McKinnon, 2000).Boththerapistsandclientswhoparticipatedinthe studyspoketotheimportanceofcollaborationthroughout thetherapeuticprocessinachievingpersonalmeaningand goalattainment.…”
Section: Discussionmentioning
confidence: 99%
“…Korumalı iş yerlerinin kişileri rekabetçi işlere dahil etme konusunda başarı oranlarının çok düşük olduğu bulgulanmıştır (Lutfiyya ve diğ. 1988 aktaran Young 2001). Yapılan başka bir çalışmada korumalı işe yerleştirme modelinin engeli olan bireylerin işe yerleştirme koşullarını iyileştirmediği ve uzun süreli uygulamaya uygun olmadığı belirtilmiştir (Thornton ve Lunt 1995, aktaran Hyde, 1998).…”
Section: Geleneksel Mesleki Rehabilitasyon Modeliunclassified